Superior Sagittal Sinus Thrombosis Complicating Typhoid Fever in a Teenager - P. O. Okunola; G. E. Ofovwe; M. T. Abiodun; C. P. Azunna (Case Reports in Pediatrics)
Cerebral venous sinus (sinovenous) thrombosis (CSVT) is a rare life-threatening disorder in childhood that is often misdiagnosed. CSVT encompasses cavernous sinus thrombosis, lateral sinus thrombosis, and superior sagittal sinus thrombosis (SSST). We present an adolescent girl who was well until two weeks earlier when she had a throbbing frontal headache and fever with chills; she later had dyspnoea, jaundice, melena stool, multiple seizures, nuchal rigidity, and monoparesis of the right lower limb a day before admission. Urine test for Salmonella typhi Vi antigen was positive, and Widal reaction was significant. Serial cranial computerized tomography scans revealed an expanding hypodense lesion in the parafalcine region consistent with SSST or a parasagittal abscess. Inadvertent left parietal limited craniectomy confirmed SSST. She recovered completely with subsequent conservative management. Beyond neuropsychiatric complications of Typhoid fever, CSVT should be highly considered when focal neurologic deficits are present.